Selected issues of information architecture - Lange-Sadzińska, Katarzyna (Wybrane problemy architektury informacji, 2012)
The article deals with the main assumptions of information architecture and information architects’ tasks. This article describes fundamental problems connected with information organization, giving distinctive names and choosing searching schemes in the information system
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 47-59
Keywords: e-commerce; information architecture; information architect; web services designing; architektura informacji; projektowanie serwisów internetowych